Phylogeography and evolutionary aspects of Indian fishes: Challenges for the future* - SILAS, E G (The Indian Journal of Animal Sciences, 2010)
A primary goal of historical ecology is to determine how communities and biological interactions develop. Interactions among species may vary geographically based on the ecological context and such variation may arise in very recent species associations. Comparative phylogeography represents a solid approach to study both the historical and ecological contexts of these interactions. Phylogeography is a field of study concerned with the principles and processes governing the geographical distributions of genealogical lineages at the inter- and intra-specific level. Mitochondrial DNA (mtDNA) has been used extensively in the last three decades as a tool for inferring the evolutionary and demographic past of both populations and species. This tool has proven invaluable for the new fields of molecular ecology and phylogeography. With the development of DNA sequencing methods and the extensive sequencing experiments undertaken in the last two decades in a wide variety of organisms, a great number of phylogenetic studies using mitochondrial gene sequences have been carried out and reported, some dealing with the use of mitochondrial genes in the establishment of different levels of phylogenetic relationships. Many studies using mtDNA as an evolutionary marker are now considered modern literature classics and demonstrate that deep insight can be obtained from studying mtDNA. Starting late in the 19th century till the first half of the 20th century, biogeographers in India were attempting to explain the apparent discontinuity in the ranges of certain plants and animals. The isolated presence of flora and fauna of Malayan origin in the Western Ghats and other south Indian hills led to a lot of speculation on the pre-history of peninsular India. Many hypotheses have been proposed and Dr. Sunder Lal Hora’s, "Satpura Hypothesis", found wide acceptance. In the light of the recent advances in molecular systematics and ecology of freshwater fishes, the paper reviews the current status of information on the genealogical lineages of Indian fishes, goal and tasks of genetic management of natural fish populations; and closes with identifying future challenges in the field.